Siblings With Deletion 22q13.3 and Trisomy 15q26 Inherited From a Maternally Balanced Translocation - Pen-Hua Su; Jia-Yuh Chen; Suh-Jen Chen (Pediatrics and Neonatology)
We describe two siblings with generalized hypotonia, expressive language delay, developmental delay, mild facial dysmorphism, and accelerated growth. In addition, the male sibling had testis dysgenesis. Cytogenetic evaluation revealed an unbalanced maternally inherited translocation t(15;22)(q26;q13.3) resulting in partial monosomy 22q and trisomy 15q. The combination of deletion 22q and duplication 15q has not been described previously.